Single CDTA-Based Current Mode All-Pass Filter and Its Applications - Neeta Pandey; Sajal K. Paul (Journal of Electrical and Computer Engineering)
This paper presents a single current difference transconductance amplifier (CDTA) based all-pass current mode filter. The proposed configuration makes use of a grounded capacitor which makes it suitable for IC implementation. Its input impedance is low and output impedance is high, hence suitable for cascading. The circuit does not use any matching constraint. The nonideality analysis of the circuit is also given. Two applications, namely, a quadrature oscillator and a high Q band pass filter are developed with the proposed circuit. The functionality of the circuit is verified with SPICE simulation using 0.35